Removal of copper from aqueous solution by citric acid modified rice straw - Che Zulzikrami, Azner Abidin; Fahmi, Muhamad Ridwan; Naimah, Ibrahim; Masitah, Hassan; Salsuwanda, Selamat; Nazerry Rosmady, Rahmat (Universiti Malaysia Pahang, 2010)
Malaysian Technical Universities Conference on Engineering and Technology organized by Universiti Malaysia Pahang in collaboration with Universiti Tun Hussein Onn Malaysia, Universiti Teknikal Malaysia Melaka & Universiti Malaysia Perlis on June 20th - 22nd, 2009, at MS Garden Hotel, Kuantan, Pahang, Malaysia.